THE EFFECT OF CANVA'S ASSISTED PJBL LEARNING MODEL WITH A GUIDED INQUIRY APPROACH ON THE CREATIVE THINKING SKILLS OF HISTORY STUDENTS: PENGARUH MODEL PEMBELAJARAN PJBL BERBANTU CANVA DENGAN PENDEKATAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN BERFIKIR KREATIF SISWA MATA PELAJARAN SEJARAH - Maulidatul Maqfiroh; Aulia Fitriany; M. Khusni Mubarok (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The purpose of this study is to find out whether students' creative thinking skills in history class improve after using the Canva-assisted PJBL Learning model with a guided inquiry approach. The location of the research was at SMA Negeri 1 Porong. This study uses quantitative research. In this study, XI-2 and XI-3 are two classes that function as control and experimental groups, respectively, in accordance with the research design, namely quasi-experimental, non-equivalent control group design. Pretest and posttest are data collection instruments using multiple-choice questions. To evaluate the hypothesis, the data were analyzed using an Independent Sample T-test. The experimental group averaged 87.14 on the posttest, while the control group averaged 80.22. The results showed that Hi was accepted and Ho was rejected based on the results of the hypothesis test, namely ttitung = 5.848 > ttable = 1.993. With the results of this study, students can improve their thinking skills while participating in interactive and imaginative learning experiences. The results of this study provide evidence that the PJBL model can improve creative thinking skills in history subjects.